Comment on surgical approaches for definitive treatment of hepatic - Akbulut, S; Sahin, TT (2020)
Echinococcus multilocularis causes alveolar echinococcosis which is a chronic, progressive zoonotic disease that mainly affects the liver. Hepatic alveolar echinococcosis is insidious and the patients are asymptomatic most of the time. Generally, it is incidentally found on imaging studies performed for other reasons. Specific symptoms may evolve if the vascular and biliary structures of the liver are affected. Hepatic alveolar echinococcosis shows a similar pattern to malignancies in terms of radiologic and clinical features. For this reason, oncological surgical principles should be applied during the resection of hepatic alveolar echinococcosis. The gold standard surgical treatment is resection with negative surgical margin. However, in patients whose radical resection is not possible other therapeutic options include palliative resection which has no benefit to the patient, and other curative major surgical options such as ex vivo liver resection, and autotransplantation and ultimately liver transplantation. The remnant liver volume has paramount importance if resection is going to be performed. For this reason, occasionally, remnant liver volume hypertrophy is induced by employing either two-stage hepatectomy or associating liver partition and portal vein ligation for staged hepatectomy. C1 [Akbulut, Sami] Inonu Univ, Fac Med, Dept Surg, TR-244280 Malatya, Turkey. Inonu Univ, Fac Med, Liver Transplant Inst, TR-244280 Malatya, Turkey.